2004
DOI: 10.1103/physrevlett.92.067402
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Photoluminescence in Semiconductor Quantum Wells: Plasma versus Excitons

Abstract: Time-resolved photoluminescence spectra after nonresonant excitation show a distinct 1s resonance, independent of the existence of bound excitons. A microscopic analysis identifies excitonic and electron-hole plasma contributions. For low temperatures and low densities the excitonic emission is extremely sensitive to even minute optically active exciton populations making it possible to extract a phase diagram for incoherent excitonic populations. 1 For a long time, photoluminescence (PL) at the spectral posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 22 publications
4
73
2
Order By: Relevance
“…Under these conditions the PL is mostly arising from excitonic recombination. 9,24 The long t r reflects the slow phonon-assisted exciton relaxation from states of large momentum k, where electron and holes were bound to form excitons, to the radiatively active states at k = 0. 14 The fast component, already seen at 13 K, has been previously observed in GaAs and tentatively attributed either to the emission of free electron-hole pairs 15 or to a rapid exciton formation mediated by LO-phonon interactions.…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions the PL is mostly arising from excitonic recombination. 9,24 The long t r reflects the slow phonon-assisted exciton relaxation from states of large momentum k, where electron and holes were bound to form excitons, to the radiatively active states at k = 0. 14 The fast component, already seen at 13 K, has been previously observed in GaAs and tentatively attributed either to the emission of free electron-hole pairs 15 or to a rapid exciton formation mediated by LO-phonon interactions.…”
Section: (B)mentioning
confidence: 99%
“…Time-resolved studies have provided a deep insight on this subject. [23][24][25][26] Using a quantum theory of the interaction between photons and an electron-hole population in GaAs QWs, Kira et al showed that a Coulomb-correlated unbound electron-hole plasma could reproduce the PL features traditionally assigned to exciton recombination. 23 Recent experiments and their interpretation [24][25][26] have led to the idea that, in QWs at low temperatures and low/medium excitation densities, excitons constitute a low percentage of the total number of excitations in the system; however, due to the large radiative recombination rate of excitons as compared to that of band-to-band transitions, the exciton emission dominates the PL spectra.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of perfectly ordered systems, a microscopic theory of semiconductor luminescence has been developed recently [15,16,17,18]. Although microscopic aspects of the Coulomb and electron-phonon interactions have been included in this approach, it is by no means trivial to extend this theory to disordered structures since one can calculate the single-particle eigenstates only for relatively small systems.…”
Section: Introductionmentioning
confidence: 99%
“…We rather perform a case study, which treats disorder and Coulomb interaction on an equal footing. Applying the theory worked out in [15,16,17,18,19,20] for ordered semiconductors we arrive at an expression that describes radiative electron-hole recombination in a disordered system without the necessity to separately modelling bound excitonic vs. separate-pair (plasma) processes (see, e.g., [14] for such an approach). The price we have to pay is to completely neglect the explicit description of phonon-induced relaxation and hopping processes.…”
Section: Introductionmentioning
confidence: 99%
“…70 K. The experimental findings indicate that intrinsic scattering processes are responsible for the intra-excitonic relaxation between radiatively forbidden states. Additional experiments applying optical absorption-based techniques such as pump-probe 32 or THz spectroscopy 33 should provide further insight.…”
mentioning
confidence: 99%